2019
DOI: 10.1155/2019/7237459
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Scheduling Method for Logistics Tasks Oriented to Intelligent Manufacturing Workshop

Abstract: Aiming at the logistics dynamic scheduling problem in an intelligent manufacturing workshop (IMW), an intelligent logistics scheduling model and response method with Automated Guided Vehicles (AGVs) based on the mode of “request-scheduling-response” were proposed, and they were integrated with Internet of Things (IoT) to meet the demands of dynamic and real time. Correspondingly, a mathematical model was developed and integrated with a double-level hybrid genetic algorithm and ant colony optimization (DLH-GA-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…On the one hand, it can be seen from constraints (10) and (11) that the shortest distances among all loading or unloading points (d E w,u and d L u,w ) are the important factors to determine the beginning time of all processing and handling tasks, while the shortest distance between all loading points depends on the decision variable of the traditional UGN design problem. On the other hand, only when the decision variables of the AGVs scheduling problem are known, the completion time C k can be determined by constraints (9) to (12), so as to evaluate the quality of the designed UGN.…”
Section: Processing and Handling Sequence Constraintsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the one hand, it can be seen from constraints (10) and (11) that the shortest distances among all loading or unloading points (d E w,u and d L u,w ) are the important factors to determine the beginning time of all processing and handling tasks, while the shortest distance between all loading points depends on the decision variable of the traditional UGN design problem. On the other hand, only when the decision variables of the AGVs scheduling problem are known, the completion time C k can be determined by constraints (9) to (12), so as to evaluate the quality of the designed UGN.…”
Section: Processing and Handling Sequence Constraintsmentioning
confidence: 99%
“…is J � J L + J E � 1920 + 800 � 2720, which is calculated by formula (1) in reference [8]. Finally, with the makespan minimization objective, the simultaneous scheduling of machines and AGVs are addressed under this UGN by taking into account the constraints of the FMS application environment, e.g., the job handling and processing sequence constraint, as shown by formula (9)- (12), and the number of AGVs constraint, as shown in formula (5). e optimal results of the traditional methods and our approach for an AGVS with different numbers of AGVs and jobs are compared in Table 7.…”
Section: Ugn Design Experiment E Layout Of An Example Fms Is Shown Inmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results confirmed that this approach was effective in small-size and medium-size problems. Xu et al 39 proposed a double-level hybrid genetic algorithm and ant colony optimization (DLH-GA-ACO) to minimize the finish time with the minimum AGVs and limited time in the logistics dynamic scheduling problem. Tai et al 40 proposed a prioritized path planning algorithm based on time windows to solve the delay problems of multiple AGVs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some companies often mistakenly believe that EDI also involves writing emails and sending order by emails. According to the data from the Czech Statistical Office, only 10% of all small enterprises, 15% of all small and medium-sized enterprises and around 30% of all large enterprises currently use EDI to exchange data with their suppliers [12,[16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%